HE ROLE OF LAND LAW IN HANDLING LAND DISPUTES BETWEEN THE GOVERNMENT AND CITIZENS - Gloria Gita Putri Ginting; Henry Aspan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Land disputes between the government and citizens are a frequent problem in Indonesia, triggered by unclear ownership, regulatory conflicts, and complex administrative procedures. This study aims to analyze the role of land law in resolving these conflicts and the effectiveness of the mechanisms implemented by the government. The method used is a normative study with an analysis of statutory documents, court decisions, and related literature. The results show that land law serves as a basis for legitimizing ownership, a guideline for dispute resolution, and a tool for enforcing community rights. However, in practice, obstacles remain, such as overlapping regulations, weak inter-agency coordination, and limited public access to legal information. The study emphasizes the importance of reforming land legal procedures, increasing transparency, and protecting community rights in all land policies. With clear and fair law enforcement, it is hoped that disputes between the government and citizens can be minimized, legal certainty guaranteed, and public trust in the land system increased. These findings provide a basis for developing more responsive, effective, and equitable land law policies for all parties.